2011
DOI: 10.1186/1471-244x-11-6
|View full text |Cite
|
Sign up to set email alerts
|

One-year risk of psychiatric hospitalization and associated treatment costs in bipolar disorder treated with atypical antipsychotics: a retrospective claims database analysis

Abstract: BackgroundThis study compared 1-year risk of psychiatric hospitalization and treatment costs in commercially insured patients with bipolar disorder, treated with aripiprazole, ziprasidone, olanzapine, quetiapine or risperidone.MethodsThis was a retrospective propensity score-matched cohort study using the Ingenix Lab/Rx integrated insurance claims dataset. Patients with bipolar disorder and 180 days of pre-index enrollment without antipsychotic exposure who received atypical antipsychotic agents were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Among the former, atypical antipsychotics (AAPs) have been increasingly used in recent years, mainly due to low rates of extra-pyramidal symptoms (some AAPs have dose dependent relationship), negative symptoms (e.g., lack of emotion, interest, and/or expression) 10 , and conditions such as tardive dyskinesia, as compared to conventional (typical) antipsychotics 1 , with evidence of efficacy as well as effectiveness in treating BPD 11,12 . AAPs have been reported to lower the rate of hospital admissions and emergency room visits, and also decrease total all-cause and mental health-related medical costs in patients with BPD [13][14][15][16] . For instance, the mean per patient reduction in costs for all-cause and mental health-related services was $1395 and $1038, respectively, for aripiprazole 16 relatively new AAP that was approved by the US Food and Drug Administration in 2009 for the treatment of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Among the former, atypical antipsychotics (AAPs) have been increasingly used in recent years, mainly due to low rates of extra-pyramidal symptoms (some AAPs have dose dependent relationship), negative symptoms (e.g., lack of emotion, interest, and/or expression) 10 , and conditions such as tardive dyskinesia, as compared to conventional (typical) antipsychotics 1 , with evidence of efficacy as well as effectiveness in treating BPD 11,12 . AAPs have been reported to lower the rate of hospital admissions and emergency room visits, and also decrease total all-cause and mental health-related medical costs in patients with BPD [13][14][15][16] . For instance, the mean per patient reduction in costs for all-cause and mental health-related services was $1395 and $1038, respectively, for aripiprazole 16 relatively new AAP that was approved by the US Food and Drug Administration in 2009 for the treatment of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparing the effectiveness of BD acute-phase and maintenance treatment with valproate versus lithium (as monotherapies or adjuncts) showed contradictory results. 2,[16][17][18][19] Aripiprazole has been consistently reported to have the most favorable hospitalization outcomes among SGAs in retrospective studies, 1,13,20,21 whereas a recent review of BD randomized controlled trials on adjunctive antipsychotics showed only one study with an SGA superior to lithium, namely quetiapine. 22 The literature on bupropion suggests that it has equivalent effectiveness to other ADs in treatment of depressive states, [23][24][25] with contradictory data on manic switch risk.…”
Section: × 10 −12mentioning
confidence: 99%
“…Hospitalization in bipolar disorder (BD) is a high-incidence outcome of great clinical and socioeconomic importance. 1 Hospital admission due to a severe mood episode occurs in 17%-40% of patients within the first year following BD acute phase treatment, 2 in 50% of patients within 4 years, 3 and in 79% of patients within 15 years. 4 The evidence on drug-dependent risk of hospitalization in BD is incomplete and contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…All antipsychotic drugs that have been studied have been found to be effective for mania,32–34 and atypical antipsychotic drugs have been promoted widely for maintenance therapy. However, randomized trials supporting this application have involved patients with uncomplicated mood disorders without the kind of comorbidity that is common in actual practice 35.…”
Section: Management Issues In Bipolar Disordermentioning
confidence: 99%